2022
DOI: 10.1002/jcla.24356
|View full text |Cite
|
Sign up to set email alerts
|

Elevated AST/ALT ratio is associated with all‐cause mortality and cancer incident

Abstract: Background:The aspartate transaminase (AST)-to-alanine aminotransferase (ALT) ratio, which is used to measure liver injury, has been found to be associated with some chronic diseases and mortality. However, its relevance to cancer incidence resulting from population-based prospective studies has rarely been reported. In this study, we investigated the correlation of the AST/ALT ratio as a possible predictor of mortality and cancer incidence. Methods: A total of 9,946 participants fulfilled the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In addition, the glucose and De Ritis ratio were negatively related and statistically significant (r=0.00, P<0.01). These results can be explained in the same contents as the results of previous studies below, De Ritis ratio of ≥1.5 suggests intrahepatic cholestasis while values ≤1.5 suggest an extrahepatic process [12] and De Ritis ratio was negatively associated with blood glucose levels [13,14].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the glucose and De Ritis ratio were negatively related and statistically significant (r=0.00, P<0.01). These results can be explained in the same contents as the results of previous studies below, De Ritis ratio of ≥1.5 suggests intrahepatic cholestasis while values ≤1.5 suggest an extrahepatic process [12] and De Ritis ratio was negatively associated with blood glucose levels [13,14].…”
Section: Discussionsupporting
confidence: 82%
“…It was first proposed for studying the etiology of hepatitis and is often used to differentiate between the different causes of liver diseases, such as the fatty liver. Currently, the AST/ALT ratio is used as a validated biomarker for nonliver diseases such as cardiovascular diseases, cancer, type 2 diabetes, and other diseases [ 35 , 36 ]. The AST/ALT ratio reflects impaired liver function; however, its elevation does not necessarily accurately reflect the severity of liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Aminotransaminases, such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), are expressed by non-cancerous and cancerous cells by different mechanisms and are strongly involved in cellular metabolism and cancer cell turnover. 37 For this reason, changes in ALT and AST values were examined in our study. First, when the ALT values were examined, it was observed that there was no difference between the cancer group and the control group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%